Kadar Lemak, Kadar Protein Dan Total Padatan Pada Susu Sapi Perah (Studi Kasus : Unit Pengolahan Susu Sapi XYZ di Padang Panjang) - Yuningsih, Ririn Marina; Arziyah, Dewi (LPPM Universitas Dharma Andalas, 2025)
Milk is one of the food ingredients that serves as a source of animal protein with high nutritional content. The nutritional content of milk is highly susceptible to damage, which is caused by the livestock itself, the environment, or the area where it is barned. The XYZ pure cow milk processing unit produces pure cow milk, the raw material of which comes from its own farm and supplies from several farming groups. This study aims to determine the quality of pure cow's milk sourced from several farming groups. The study used purposive sampling, with samples taken from five farming groups, namely groups A, B, C, D, and E. The research results show the fat content, protein content, and total solids of pure milk from the five farming groups in accordance with SNI. Group C had the highest values, with a fat content of 6.38%, a protein content of 2.82%, and total solids of 8.7%.